Mobility, Internationalisation, Higher Education: European Challenges - Maria da Conceição Pereira Ramos (2014)
Abstract With an increase in global competition among universities and national higher education systems, educational programs desire to offer compatible content without losing their competitive advantage. Because of this balance, the issue of convergence, along with its benefits and limits, has emerged. The Handbook of Research on Trends in European Higher Education Convergence aims to identify the indicators that meet the consensus of the academic community and higher education management experts. Analyzing the recognized trends within the publication and concluding which measures should be taken to improve convergence pace and avoid potential pitfalls; this reference book is a useful resource for academics and students, as well as specialists, policy makers, and professionals connected with the educational sector. (c) 2014 by IGI Global. All rights reserved.